Comprehensive Inventory and Medicinal Potential of Macroalgae in Cibuaya Beach Coastal Ecosystem, Ujung Genteng, Sukabumi - Effendi, Alvira Noer; Fadhillah, Hilwa Syifa; Khairunisah, Siti Delvia; de’Ornay, Amelia Rina Nogo; Sari, Bunga Anggreini; Handayani , Sri (Universitas Nasional Jakarta, 2024)
The potential for macroalgae diversity along the coast of Cibuaya Beach, Pangumbahan Village, Ujung Genteng, Sukabumi Regency, West Java, is illustrated in this study. Macroalgae, recognized as integral components of marine ecosystems, have garnered attention due to their substantial economic value and ecological benefits. This study aims to conduct an inventory and identification of macroalgae in this specific locale. The quadratic transect method was employed to provide a comprehensive overview of macroalgae types in the area. The identification results revealed the presence of 25 macroalgae types from 19 tribes and 3 divisions. The diversity assessment yielded a moderate value (2.4) at station 1, while station 2 exhibited a lower diversity level with a value of 1.06, indicating higher species diversity at station 1. Analysis of dominance, as measured by the dominance index, indicated a low level (0.13) at station 1 and a medium level (0.59) at station 2, with Boergesenia forbesii emerging as the dominant type at both stations. These findings contribute to a deeper understanding of macroalgae diversity potential along the Cibuaya Coast, providing crucial insights to support marine conservation efforts in the region and serving as a cornerstone for further ecological investigations. Furthermore, considering the proven medicinal potential of macroalgae in prior studies, these findings underscore the significance of this research in the realm of potential drug development and nature-based therapies.